FINDINGS OF GENITAL AND MENTAL PHYSICAL EXAMINATION IN FEMALE VICTTIMS OF SEXUAL CRIMES - Widiagung, Anak Agung Gede Bayu Rajendra; Henky, Henky; Alit, Ida Bagus Putu; Yulianti, Kunthi; Setyawati, Lely (E-Jurnal Medika Udayana; Vol 13 No 07 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i07.P17, 2024)
Cases of sexual violence in Indonesia based on the Annual Records of Komnas Perempuan are still quite high. One form of sexual violence is rape. The act of rape can be proven from the results of a physical examination to look for evidence in the form of violence and sexual intercourse. In addition to physical examination, mental health examination is also carried out to see the impact of the incident experienced by the victim. This study aims to find out what are the findings on physical and mental examinations of female victims of sexual crimes. This study used a descriptive method with a cross-sectional research design and used total sampling techniques as a sampling technique. The results of this study from 50 victims found that the age group that experienced the most sexual crimes was late adolescence (34.00%). The findings in victims were dominated by only signs of sexual intercourse (48.00%). The location of the injuries experienced by the most victims was found to be in the genital area only, which was as much as (52.00%) with the most types of genital injuries being lacerations (54.00%). The most mental disorders experienced by victims are in the form of only depression (4.00%). Only (16.00%) victims found their court decision data at the Denpasar District Court. It can be concluded from this study that the findings of penetration marks in the form of injuries to the victim's genitals alone dominate, namely as many as (70.00%), only (4.00%) victims who have penetration marks accompanied by ejaculatory marks. The genital injuries suffered by the victims (54.00%) were lacerations. Mental disorders found in victims in the form of depression as much as (4.00%), while victims without findings of mental disorders as much as (86.00%).